Quantum Dots: Origin of Positive Aging in Quantum‐Dot Light‐Emitting Diodes (Adv. Sci. 10/2018). Issue 10 (17th October 2018) - Su, Qiang; Sun, Yizhe; Zhang, Heng; Chen, Shuming
Abstract : In the movie "The Curious Case of Benjamin Button", Benjamin Button becomes younger and younger as time passes by. He experiences a "positive aging" life, which seems impossible in human beings, but becomes a reality in quantum‐dot light‐emitting diodes (QLEDs). In article number1800549, Shuming Chen and co‐workers report positive aging in QLEDs, i.e., efficiency increased with time. They disclose the origin of positive aging and provide a new insight into the exciton quenching mechanisms, which would be useful for constructing efficient QLED devices.